The Physical Behaviour Intensity Spectrum and Body Mass Index in School-Aged Youth: A Compositional Analysis of Pooled Individual Participant Data - Fairclough, Stuart J; Hurter, Liezel; Dumuid, Dorothea; Gába, Ales; Rowlands, Alex V; Cruz, Borja Del Pozo; Cox, Ashley; Crotti, Matteo; Foweather, Lawrence; Graves, Lee E F; Jones, Owen; McCann, Deborah A; et al. (International journal of environmental research and public health, 2022)
We examined the compositional associations between the intensity spectrum derived from incremental acceleration intensity bands and the body mass index (BMI) z-score in youth, and investigated the estimated differences in BMI z-score following time reallocations between intensity bands. School-aged youth from 63 schools wore wrist accelerometers, and data of 1453 participants (57.5% girls) were analysed. Nine acceleration intensity bands (range: 0-50 mg to ≥700 mg) were used to generate time-use compositions. Multivariate regression assessed the associations between intensity band compositions and BMI z-scores. Compositional isotemporal substitution estimated the differences in BMI z-score following time reallocations between intensity bands. The ≥700 mg intensity bandwas strongly and inversely associated with BMI z-score (p < 0.001). The estimated differences in BMI z-score when 5 min were reallocated to and from the ≥700 mg band and reallocated equally among the remaining bands were -0.28 and 0.44, respectively (boys), and -0.39 and 1.06, respectively (girls). The time in the ≥700 mg intensity band was significantly associated with BMI z-score, irrespective of sex. When even modest durations of time in this band were reallocated, the asymmetrical estimated differences in BMI z-score were clinically meaningful. The findings highlight the utility of the full physical activity intensity spectrum over a priori-determined absolute intensity cut-point approaches.
Keywords: Sedentary Behavior; Female; dítě; ženské pohlaví; sedavý životní styl; Adolescent; lidé; cvičení; školy; Schools; Acceleration; Male; index tělesné hmotnosti; Child; zrychlení; mužské pohlaví; Body Mass Index; Exercise; mladiství; Humans